2021
DOI: 10.1161/atvbaha.120.314516
|View full text |Cite
|
Sign up to set email alerts
|

Novel LCAT (Lecithin:Cholesterol Acyltransferase) Activator DS-8190a Prevents the Progression of Plaque Accumulation in Atherosclerosis Models

Abstract: Objective: Enhancement of LCAT (lecithin:cholesterol acyltransferase) activity has possibility to be beneficial for atherosclerosis. To evaluate this concept, we characterized our novel, orally administered, small-molecule LCAT activator DS-8190a, which was created from high-throughput screening and subsequent derivatization. We also focused on its mechanism of LCAT activation and the therapeutic activity with improvement of HDL (high-density lipoprotein) functionality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…CUC was significantly enhanced in the presence of rhLCAT. Recently, therapeutic concepts for coronary heart disease and atherosclerosis using recombinant LCAT protein or an LCAT activator have been proposed, and dose-dependent increases in HDL-C along with the enhancement of cholesterol efflux or in vivo reverse cholesterol transport (RCT) have been demonstrated [ 30 , 43 ]. Considering the enhancement of CUC in the presence of rhLCAT, as shown in this study, CUC may change in response to these molecules, in a manner similar to cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…CUC was significantly enhanced in the presence of rhLCAT. Recently, therapeutic concepts for coronary heart disease and atherosclerosis using recombinant LCAT protein or an LCAT activator have been proposed, and dose-dependent increases in HDL-C along with the enhancement of cholesterol efflux or in vivo reverse cholesterol transport (RCT) have been demonstrated [ 30 , 43 ]. Considering the enhancement of CUC in the presence of rhLCAT, as shown in this study, CUC may change in response to these molecules, in a manner similar to cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of DS-8190A also stimulated RCT process in primate cynomolgus monkeys. 363 These studies suggest that LCAT activation may help to reduce residual risk of ASCVD.…”
Section: Cholesterol-related Diseases and Interventionsmentioning
confidence: 96%
“…It has been found that compound A (3-(5-(ethylthio)-1,3,4-thiadiazol-2-ylthio)pyrazine-2-carbonitrile) covalently binds to Cys31 at the active site of LCAT, increases the levels of CE and HDL-C in the plasma of mice and hamsters, and develops sulfhydryl reactive β -lactam as a new type of LCAT activator [ 75 , 76 ]. Recent studies have found that a new oral small molecule LCAT activator, DS-8190, increased HDL-C and reduced the area of atherosclerotic lesions by directly binding to human LCAT protein [ 77 ].…”
Section: Lcatmentioning
confidence: 99%